/a?/ Recognition: Maximizing English Sounds and Spelling Exercises in Pronunciation Class - Ana Ahsana El-Sulukiyyah; Dewi Masitho Istiqomah (Universitas Islam Negeri (UIN) Mataram, 2021)
Pronunciation is an essential part of language learning. We need to possess intelligible pronunciation to communicate effectively. The study of pronunciation sometimes becomes fatigued and challenging for teachers. They should not employ a repeat after me technique but include senses, sights, or even move to teach pronunciation. Sounds and spelling exercises could be helpful for effective pronunciation practice because they relate to phonemic awareness or sound recognition. This descriptive qualitative research used sounds and spelling exercises in pronunciation practices involving 42 students, focusing on/a?/ recognition at an Indonesian English Education Study Program. Students were given the exercises of sounds and spelling and then observed the progress of pronunciation ability. The results showed that this exercise could help students remedy their pronunciation, especially in /a?/ sounds. The significant improvement indicated the effectiveness of the practice because it is related to phonemic awareness, which allowed them to distinguish the sounds and the letters. As students knew and could predict the sounds in the written words, they precisely corrected their pronunciation, especially in words consisting of /a?/ sounds.